EFFECTS OF RESULT-BASED CAPABILITY BUILDING PROGRAM ON THE RESEARCH COMPETENCY, QUALITY AND PRODUCTIVITY OF PUBLIC HIGH SCHOOL TEACHERS - Ramos, Warren A. (PEOPLE: International Journal of Social Sciences, 2017)
In the new rationalized structure of the Department of Education (DepEd), programs, projects and activities are expected to be result-based. In the past years, capability building program specifically on research focused only on physical targets as the success indicator. Hence, the expected result in the capability program are long-term and impactful primarily on the competencies, quality and sustainability. This study was conducted to determine the impact of result-based research capability building program on the competency, quality and productivity among 78 public junior high school teachers in DepEd-National Capital Region. An adapted research instrument was used to measure the research competency of the participants before and after the third phase of the program. After one month, their outputs were analyzed using the adapted rubrics for action research proposals. Furthermore, the research competencies of participants increased from low to high after the training. It also revealed using the t -test that there were significant differences in the research competency of the participants. The assessed action research proposals were rated “satisfactory” in terms of quality. Consequently, the research productivity in terms of physical targets got 100% because of the proposals collaboratively crafted and submitted by the participants.Therefore, the program was effective and it produced quality research proposals in the second revision. Finally, this study recommends that teachers must be empowered by the necessary competency in conducting action research with the mechanism of coaching, mentoring and consultation with the school heads and experts from partner Higher Education Institutions. This participative approach in research ensures that the effectiveness and impact of the program are geared towards the attainment of DepEd Vision, Mission and Objectives.